OS X Mavericks - Beighley, Lynn (Peachpit learning series., 2014)
If you are new to OS X, you'll learn the basics of how to use OS X efficiently and joyfully. From there, you can move on to customize Mavericks to suit the way you work. And if you've been using OS X already, you'll learn how to get the most out of iCloud integration, Notifications, Maps, iBooks, Finder tabs, multiple displays, and more.